Desenvolvimento de biocatalisadores enzimáticos pela estabilização de Lecitase Ultra em suporte macroporoso - Pinheiro, Maísa Pessoa (2018)
The aim of this work was to immobilize Lecitase Ultra ® (LU) onto Immobead-350 (IB-350) support through different immobilization protocols, using unmodified support and modified support (activated with functional groups by several strategies) and also through immobilization by cross-linking. The different immobilization strategies in this work were carried out in order to modulate enzyme properties and to evaluate the effects of three parameters in the final enzyme conformation and biocatalyst properties: incubation time; different pH values in the ionization of functional groups of the enzyme and of the support; and blocking stage. In addition, biocatalysts formed by immobilization of LU onto supports activated with aldehyde, divinylsulfone or glutaraldehyde groups were evaluated for their catalytic versatility versus two different substrates. The results showed that all biocatalysts were active versus the hydrolysis of p-nitrophenyl butyrate (p-NPB), but Leci-GLU showed the highest derivative activity (17.39 U / g) and was the most stable preparation both at 50 °C (1.9 h) and in the presence of 30% acetonitrile (42.6 h). The derivatives were also tested for operational and storage stability. In this first assay, the biocatalysts maintained 100 % of their initial activity during 10 consecutive reaction cycles, while in storage stability all the derivatives remained with 80 % of the initial activity in 30 days of storage at 4 °C, only Leci-DVS reduced about 50 % of its initial activity. In order to test catalytic versatility, biocatalysts were applied in hydrolysis (methyl mandelate substrate) and transesterification (acetylation of benzyl alcohol) reactions. The product obtained from this last reaction is known as jasmine aroma and has high commercial value, in addition, it can be used in detergent and perfume industry. In relation to methyl mandelate hydrolysis, the biocatalysts were tested at different reaction conditions (pHs 5, 7 and 9) and the highest activity was obtained with the Leci-crossA derivative at pH 7 (28.4 U / mg). In benzyl alcohol acetylation the biocatalyst with the highest activity was Leci-GLU (2.1 mg).